Effects of transglutaminase on the proximal and textural properties of gluten-free bread of sorghum and quinoa - Rodríguez Castillejos, Guadalupe; Lizarazo Ortega, Cristian; González Pérez, Ana; Montes García, Noé; Ruíz Salazar, Régulo (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2018)
Gluten is found in cereals such as wheat, barley and rye. Some people are genetically predisposed to gluten intolerance, so there is a growing demand for gluten-free bakery products with high quality proteins. Replacing gluten represents a technological challenge, as it requires the use of additives, primarily hydrocolloids or enzymes, to improve the mechanical properties of dough. In this study, we evaluated the effect of microbial transglutaminase (MTG) on the chemical properties of sorghum bread enriched with quinoa. Bread was prepared by mixing, fermenting and baking sorghum flour (80%) and quinoa flour (20%), with the addition of 0.5% MTG. Control bread with no added enzyme was prepared too. The results showed that the content of protein (14.61%), fiber (16.04%), minerals (2.45%) and carbohydrates were higher in the bread that contained transglutaminase, while the fat content was higher in the bread without the enzyme (14.14%). The analysis of textural parameters such as chewiness, gumminess and cohesiveness showed a significant difference in the MTG bread. These results suggest that adding MTG to sorghum-quinoa bread improves its nutritional properties by increasing its content of protein and fiber, resulting in a gluten-free product of high nutritional value.